Alnus subgenus Alnus in the Eocene of western North America based on leaves, associated catkins, pollen, and fruits1. Issue 11 (1st November 2014) - Liu, Xiaoyan; Manchester, Steven R.; Jin, Jianhua
Abstract : Premise of the study: The fossil record of alder ( Alnus ) is well known in the Cenozoic deposits throughout the northern hemisphere, based on numerous reports of the distinctive pollen, cone‐like infructescences, staminate inflorescences, and leaves. However, our understanding of the systematic position of these fossils relative to the modern phylogeny of the genus has been limited because most fossils were described from only one organ. Methods: We examined well‐preserved leaves and associated fruiting and staminate catkins from the middle Eocene, Clarno Formation, Oregon, USA by stereomicroscopy. In situ and dispersed pollen were cleaned with HF and acetolized for light and scanning electron microscopy. Key results: We reconstructed a new extinct species based on multiple organs and discuss significant phytogeographic and phylogenetic implications for Alnus . Alnus clarnoensis sp. nov. is described based on serrate leaves with 1–4 small teeth between each primary tooth, associated cone‐like fruiting catkins with fruits in situ, and associated slender pollen catkins bearing in situ 3‐ to 6‐pored pollen with arci between the pores. Combined investigations of each organ indicate that they probably derive from the same species and can be confidently attributed to subgenus Alnus Furlow based on leaf architecture and pollen pore number frequency. Conclusions: The Clarno fossils are most similar to the extant North American species of subgenus Alnus rather than to those from Asia and Europe, indicating that this modern subgenus was already distinct by the middle Eocene and that the intercontinental migration likely occurred earlier.